Le donne dei principi nel Lazio protostorico (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2009)
This paper focuses on the role of women in the societies of ancient Latium. In this contribution many cases of burials are presented to illuminate the importance of their role. The analysis of these burials, in terms of grave goods and their setting within the grave, is carried out in comparison with  Etruscan and other pre-Roman areas and with attention to Greek and Roman literary sources, in order to present some specific aspects and activities that involved women in the aristocratic society of the Orientalizing period.